Individual 3D-printed fixation masks for radiotherapy: first clinical experiences - Mattke, Matthias; Rath, Daniel; Häfner, Matthias; Unterhinninghofen, Roland; Sterzing, Florian; Debus, Jürgen; Giesel, Frederik L. (International journal of computer assisted radiology and surgery, 2021)
To show the feasibility of 3D-printed fixation masks for whole brain radiation therapy in a clinical setting and perform a first comparison to an established thermoplastic mask system.